PERTANGGUNGJAWABAN TINDAK PIDANA PENCURIAN BARANG MILIK PENUMPANG (STUDI KASUS PENCURIAN BARANG PENUMPANG BUS ROSALIA INDAH) - Pratama, Renaldi Raka; Sumanto, Anatasia Ruli (Universitas Kapuas, 2025)
Theft is one type of crime that often occurs in various places, including in the transportation process. Theft of passengers' belongings during transportation by an Otobus Company (PO) is a problem that is often faced. This study aims to analyze the responsibility of PO Rosalia Indah for the loss of passenger goods, especially in the case of theft in their bus fleet. The method used is normative legal research that refers to primary and secondary basic materials through literature study and documentary study. Based on Indonesian laws and regulations, including the Criminal Code, KUHD, Law No. 22 of 2009 on Road Traffic and Transportation, and Law No. 8 of 1999 on Consumer Protection, POs are liable for passenger losses if negligence is proven, even if there is a clause in the ticket stating otherwise. The results show that passengers have a strong legal basis to claim damages, and PO Rosalia Indah should improve its security and service standards to ensure the safety of passengers' luggage. This is important not only for legal compliance but also to maintain customer trust and satisfaction.